Learning from Power Sector Reform : The Case of The Philippines - Bacon, Robert (World Bank, Washington, DC, 2019)
The Philippines power sector underwent a substantial and largely complete reform process. Following a severe shortage of supply in the late 1980s and the Asian Financial crisis of 1997, which made the dollar-denominated debt of the National Power Corporation extremely burdensome, the Electric Power Industry Reform Act was passed in 2001. This was intended to improve the quality of service and reduce power tariffs via the introduction of private participation and competition at the wholesale and retail levels. Although the implementation of the full reform program took longer than originally expected, the unwavering support given to the reform agenda by successive presidents of the country ensured that the planned steps had all been completed by 2013. At that time, retail competition and open access for consumers in Luzon and Visayas of more than one megawatt were introduced. The reform process was not impeded by complications that would have arisen if consumer subsidies had been endemic, but retail prices are even higher than might have been expected in the absence of subsidies, due to domestic taxation and the presence of some inefficiencies that have not yet been eliminated by the onset of competition.